PICKERING EMULSION TECHNOLOGY IN FABRICATE CELLULOSE FOAM FROM OIL PALM EMPTY FRUIT BUNCH WASTE - Putri Amanda; Syarifah Nabila; Ismadi Ismadi; Deni Purnomo; Nanang Masruchin (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2021)
PICKERING EMULSION TECHNOLOGY IN FABRICATE CELLULOSE FOAM FROM OILPALM EMPTY FRUIT BUNCH WASTE. Cellulose from the oil palm empty fruit bunch (OPEFB) waste can make a porous material. This study aims to make cellulose foam with Pickering emulsion technology used cellulose nanofiber as a Pickering agent. The mechanism of Pickering emulsion is learned from foamability and stability of foam in the presence of various concentrations of surfactant. The result showed that using Pickering emulsion technology only needed surfactant with a small concentration to improve foamability and stability. The addition of CNF indeed improved the stability and foamability with the Pickering effect. The stability test shows that the foam stabilized with CNF appeared to be relatively stable. In contrast to the CNF free system, the foams were collapse in three days tested. Structures of foam was characterized using an optical microscope and showed that the foam was composed into two- or three dimensional microstructures formed by gas bubble of wet foam in random orientations. This process generated the lightweight Cellulose foam from OPEFB waste, with a density of 0.07 g/cm3. Using Pickering emulsion technology to make cellulose foam can be one way to overcome OPEFB waste and this foam is potential for various applications.